Effect of different disinfectants on preventing asymptomatic bacteriuria and catheter-related urinary tract infection: a network meta-analysis - Sun, Zhi Hong; Ma, Xue Wei; Sun, Wei; Wei, Ying Ji; Li, Yi Zhen; Wang, Dan; Zhou, Chang Xi; Xu, Guo Gang; Zhang, Gui Zhi (Frontiers in Urology, 2023)
Objective To analyze the effect of different types of disinfectants for perineum and urethral meatus cleaning in preventing catheter-associated asymptomatic bacteriuria and catheter-associated urinary tract infection (CAUTI). Methods Chinese and English databases were searched to collect randomized controlled trials (RCTs) of different disinfectants for perineum and urethral meatus cleaning to prevent CAUTI, and the positive rates of urine culture with different cleaning methods were contrasted by network meta-analysis. Results A total of 18 RCTs were included in this study to analyze the effect of 10 disinfectants in preventing CAUTI. The disinfectants were 0.1% chlorhexidine (CHG), 0.5% CHG, 2% CHG, 0.1% benzalkonium bromide (DBDAB), 0.05% iodophor, 0.5% iodophor, acidic oxidizing potential water (EOW), normal saline (NS), Shehuang lotion, and sterile water. Meta-analysis showed that the positive rates of urine culture in the 0.5% CHG cluster, EOW cluster, 0.5% iodophor cluster, and Shehuang lotion cluster were remarkably lower than that in the 0.1% DBDAB cluster (P < 0.05). The positive rate of urine culture in the 0.5% CHG cluster was remarkably lower than that in the 0.05% iodophor cluster (P < 0.05), whereas the positive rates of urine culture in the 0.5% CHG cluster, 0.5% iodophor cluster, Shehuang lotion cluster, and EOW were remarkably lower than that in the normal saline cluster (P < 0.05). The positive rate of urine culture in the 0.5% CHG cluster and EOW cluster were remarkably lower than those in the sterile water cluster (P < 0.05). The results of the area under the cumulative ranking probability plot (SUCRA) analysis showed that the probability ranking of the preventive effect of different disinfectants was as follows: 0.5% CHG > Shehuang lotion > EOW > 0.5% Iodophor > 2% CHG > 0.1% CHG > 0.05% Iodophor > Sterile Water > 0.1% DBDAB > Saline. Conclusion 0.5% CHG, Shehuang lotion, EOW, and 0.5% iodophor can be used to clean the perineum and urethral meatus in patients with indwelling catheters. Systematic review registration Chinese Clinical Trial Registry (ChiCTR), identifier ChiCTR2100052260.